PENGARUH KONSENTRASI RAGI Saccharomyces cerevisiae DAN LAMA FERMENTASI TERHADAP KUALITAS CUKA TOMI-TOMI (Flacourtia inermis) - Sandra J Nendissa; Rachel Breemer; Nikholaus Melamas (Universitas Pattimura, 2015)
This objectives of this research were both to study and determine the best level of concentration of yeast Saccharomyces cereviseae and period of fermentation on the quality of tomi-tomi vinegar (Flacourtia inermis). A completely randomized experimental design with two factors of treatment was applied in this research. The first factor was concentration of yeast S. cereviseae having four levels of tretament, i.e.: without the addition of yeast 0.5, 1 and 1.5 g yeast. The second factor was period fermentation with 1, 2, 3, 4, and 5 weeks. The result indicated that the concentration of yeast S. cereviseae 1.5 g and period fermentation 5 week produced a good tomi-tomi vinegar with total acids 51.22%, total dissolved solids 8.35, total sugar 8.07% and pH 5.40.